COVID-19 and alarming dengue co-epidemics in the dilapidated healthcare system in Pakistan: Where to focus!. Issue 4 (April 2022) - Khurram, Muhammad; Ali, Ghadir; Awan, Usman Ayub; Afzal, Muhammad Sohail
Highlights: The healthcare sector should set aside a portion of its budget to deal with the dengue and COVID-19 co-epidemics. In Pakistan, there is an urgent need to re-evaluate awareness efforts to ensure their effectiveness in the future. Policymakers should formulate policies to reduce the cost of vector control, patient care, and genotype evolution.